2017
DOI: 10.1038/srep44484
|View full text |Cite
|
Sign up to set email alerts
|

MdHIR proteins repress anthocyanin accumulation by interacting with the MdJAZ2 protein to inhibit its degradation in apples

Abstract: In higher plants, jasmonate ZIM-domain (JAZ) proteins negatively regulate the biosynthesis of anthocyanins by interacting with bHLH transcription factors. However, it is largely unknown if and how other regulators are involved in this process. In this study, the apple MdJAZ2 protein was characterized in regards to its function in the negative regulation of anthocyanin accumulation and peel coloration. MdJAZ2 was used as a bait to screen a cDNA library using the yeast two-hybrid method. The hypersensitive induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…There was also a putative TLLLFR-type repressor motif at the C-terminnus of VvMYBC2L2 , which was also found in the flavonoid repressor AtMYBL2 [21]. Compared with other R2R3 MYB proteins, VvMYBC2L2 has strong similarities with VvMYBC2L3 , MdMYB111 and FaMYB1 which negatively regulate the flavonoid pathway [23,25,31]. These results suggested that VvMYBC2L2 may play a role as an active transcriptional repressor of flavonoid biosynthesis in grapevine.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a putative TLLLFR-type repressor motif at the C-terminnus of VvMYBC2L2 , which was also found in the flavonoid repressor AtMYBL2 [21]. Compared with other R2R3 MYB proteins, VvMYBC2L2 has strong similarities with VvMYBC2L3 , MdMYB111 and FaMYB1 which negatively regulate the flavonoid pathway [23,25,31]. These results suggested that VvMYBC2L2 may play a role as an active transcriptional repressor of flavonoid biosynthesis in grapevine.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the JA pathway is related to the synthesis of anthocyanin because it upregulates the genes in charge of the synthesis of anthocyanins (Shan et al, 2009). In their study, Chen et al (2017) found that the HIR protein interacts with the JAZ-HLH complex and acts as a negative regulator of the accumulation of anthocyanins in apple.…”
Section: Flower Color Cotyledon Color and Stem Colormentioning
confidence: 99%
“…Recently, the hypersensitive induced reaction (HIR) protein was found to interact with the jasmonate ZIM-domain (JAZ) protein during anthocyanin biosynthesis (Chen et al, 2017). It is known that the JA pathway is related to the synthesis of anthocyanin because it upregulates the genes in charge of the synthesis of anthocyanins (Shan et al, 2009).…”
Section: Flower Color Cotyledon Color and Stem Colormentioning
confidence: 99%
“…Intriguingly, through joint analysis using RNA-seq and metabolomics, we found that HIR3 was highly correlated with anthocyanin petunidin 3- O -glucoside (pme3391) at a later stage of F. graminearum infection in resistant line K09, revealing the possibility of HIR3 and anthocyanin network in the regulation of GSR resistance. A recent study showed that apple HIR protein MdHIR4 could suppress anthocyanin accumulation via interacting with MdJAZ2 protein ( Chen et al, 2017 ). It will be interesting to investigate whether HIR3 gene regulates anthocyanin accumulation, or anthocyanin impacts HIR3 expression, upon F. graminearum infection.…”
Section: Discussionmentioning
confidence: 99%